Preparation of Tin Using Wet Method - Kasscr, N.W.; Kasscr, N.W.; Al-Mukhtar, M.N.; Jaralla, A. A.; Hadi, H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The preparation of tin metal from stannous chloride solution by wet method in the presence of aluminum powder as a reducing agent is studied. The preparation is commenced through a reduction step in the presence of reducing agent followed by smelting step at elevated temperature in a programmable electrical furnace. In the reduction step, preliminary experiments are conducted to study the effect of initial acidity, time of addition of the aluminum powder and excess amount of reducing agent on the conversion of stannous to tin metal. Three different parameters are studied through smelting step, these are : heating rate, temperature and residence time. To characterize the product, different instrumental analyses are used: - X-ray diffraction to check the existence of tin after reduction step in the agglomerates and the existence of tin oxide after smelting step and in the remaining slag. - Atomic absorption to determine the quantity of tin in the agglomerates after reduction step. - Diffraction scanning calorimetry (DSC) for identification. - Electron scanning to study the effect of smelting step variables on the crystal structure of the prepared tin. Reasonably between the three studied variables, only temperature shows a significant influence on the productivity of tin. Studying the crystal structure of the produced tin confirms the enormous effect of temperature on the shape and size of grain structure